Applying the quarter-hour rule: Can people with insomnia accurately estimate 15-min periods during the sleep-onset phase? - Harrow, L; Espie, C (2010)
Summary The 'quarter-hour rule' (QHR) instructs the person with insomnia to get out of bed after 15 min of wakefulness and return to bed only when sleep feels imminent. Recent research has identified that sleep can be significantly improved using this simple intervention (Malaffo and Espie, Sleep, 27(s), 2004, 280; Sleep, 29 (s), 2006, 257), but successful implementation depends on estimating time without clock monitoring, and the insomnia literature indicates poor time perception is a maintaining factor in primary insomnia (Harvey, Behav. Res. Ther., 40, 2002, 869). This study expands upon previous research with the aim of identifying whether people with insomnia can accurately perceive a 15-min interval during the sleep-onset period, and therefore successfully implements the QHR. A mixed models anova design was applied with between-participants factor of group (insomnia versus good sleepers) and within-participants factor of context (night versus day). Results indicated no differences between groups and contexts on time estimation tasks. This was despite an increase in arousal in the night context for both groups, and tentative support for the impact of arousal in inducing underestimations of time. These results provide promising support for the successful application of the QHR in people with insomnia. The results are discussed in terms of whether the design employed successfully accessed the processes that are involved in distorting time perception in insomnia. Suggestions for future research are provided and limitations of the current study discussed. © 2009 European Sleep Research Society.